Answer

Verified

432k+ views

**Hint:**Here we have to imagine a hypothetical ring of radius X and thickness dx, the hypothetical ring is inside the ring. We have to find the electric field of the hypothetical ring first and then we have to integrate the electric field to get the electric field of the real ring on the point p on the y-axis.

**Formula used:**

The formula for finding out the coefficient of performance is given below.

$E = \dfrac{{Kqy}}{{{{({x^2} + {y^2})}^{3/2}}}}$

Here,

$E$= Electric field

$K$= Proportionality constant ($9 \times {10^9}$$N$${m^2}/{C^2}$)

$q$= Charge

$x$= Distance in the direction of the x axis.

$y$= Distance in the direction of y axis

The formula for charge on the hypothetical ring is

dq = $\sigma $ $\times$ 2πx;

$\sigma $= Surface charge density.

$x$ = Radius of the hypothetical ring

$2πx$ = Circumference of the hypothetical ring.

**Complete step by step answer:**

Step 1: Look at the below picture. Here, apart from the Big ring whose radius is ${R_1}$ and ${R_2}$. We have to draw a hypothetical ring whose radius is x and thickness is dx. We have to find the charge on the hypothetical ring.

The charge on the hypothetical ring is

dq = $\sigma $× 2πx;

Now, we know the electric field due to a ring, which is

$E = \dfrac{{Kqy}}{{{{({x^2} + {y^2})}^{3/2}}}}$

So, for a small charge dq, the equation becomes,

$E = \dfrac{{Kdqy}}{{{{({x^2} + {y^2})}^{3/2}}}}$

Put the value of dq in the above equation

$E = \dfrac{{K(\sigma \times 2\pi x).y}}{{{{({x^2} + {y^2})}^{3/2}}}}$

Step 2: Calculating the total electric field of the ring by integrating the equation.

$E = \dfrac{{(\sigma \times 2\pi x).y}}{{4\pi {\varepsilon _o}{{({x^2} + {y^2})}^{3/2}}}}$; (Here k =$\dfrac{1}{{4\pi {\varepsilon _o}}}$=$9 \times {10^9}$)

After solving the above equation we get

$E = \dfrac{{\sigma. x.y}}{{2{\varepsilon _o}{{({x^2} + {y^2})}^{3/2}}}}$

Now, we integrate the equation from ${R_1}$to${R_2}$

\[E = \dfrac{{\sigma y}}{{2{\varepsilon _o}}}\int_{{R_1}}^{{R_2}} {\dfrac{x}{{{{({x^2} + {y^2})}^{3/2}}}}} dx\]

Let ${x^2} + {y^2}$=${p^2}$;

Now differentiate ${x^2}$ w.r.t x and ${p^2}$w.r.t p, we get

${x^2} + {y^2}$=${p^2}$; …. ($\dfrac{{d{x^n}}}{{dx}} = n{x^{n - 1}}$)

Differentiate each variable,

$\dfrac{{d{x^2}}}{{dx}} + \dfrac{{d{y^2}}}{{dx}} = \dfrac{{d{p^2}}}{{dp}}$; ….($\dfrac{{d{x^2}}}{{dx}} = 2x$); ($d{x^2} = 2xdx$)

Here$\dfrac{{d{y^2}}}{{dx}} = 0$; because of a different variable in the numerator,

$2x\,dx + 0 = 2p\,dp$;

$2x\,dx = 2p\,dp$;

Here, we have established a relation between xdx and pdp.

Now, put ${x^2} + {y^2}$=${p^2}$in the given below equation,

\[E = \dfrac{{\sigma y}}{{2{\varepsilon _o}}}\int_{{R_1}}^{{R_2}} {\dfrac{x}{{{{({x^2} + {y^2})}^{3/2}}}}} dx\]

Write the above equation in terms of $p$,

\[E = \dfrac{{\sigma y}}{{2{\varepsilon _o}}}\int_{{R_1}}^{{R_2}} {\dfrac{p}{{{{({p^2})}^{3/2}}}}} dp\]

solving the above equation,

\[E = \dfrac{{\sigma y}}{{2{\varepsilon _o}}}\int_{{R_1}}^{{R_2}} {\dfrac{p}{{{p^{(3)}}}}} dp\]

Simplify the above equation

\[E = \dfrac{{\sigma y}}{{2{\varepsilon _o}}}\int_{{R_1}}^{{R_2}} {\dfrac{1}{{{p^{(2)}}}}} dp\] ….($\int {{p^{( - n)}}dp = \dfrac{{{p^{( - n) + 1}}}}{{( - n) + 1}}} $)

Solving integration,

\[E = \dfrac{{\sigma y}}{{2{\varepsilon _o}}}\left[ {\dfrac{{{p^{( - 2) + 1}}}}{{( - 2) + 1}}} \right]_{{R_1}}^{{R_2}}\]

Simplify further,

\[E = \dfrac{{\sigma y}}{{2{\varepsilon _o}}}\left[ { - {p^{ - 1}}} \right]_{{R_1}}^{{R_2}}\]

Put the value of p i.e. p =\[{( - \sqrt {{x^2} + {y^2}} )^{ - 1}}\]

\[E = \dfrac{{\sigma y}}{{2{\varepsilon _o}}}\left[ {{{( - \sqrt {{x^2} + {y^2}} )}^{ - 1}}} \right]_{{R_1}}^{{R_2}}\]

\[E = \dfrac{{\sigma y}}{{2{\varepsilon _o}}}\left[ {\dfrac{1}{{( - \sqrt {{x^2} + {y^2}} )}}} \right]_{{R_1}}^{{R_2}}\]

Put the upper limit (${R_2}$) in place of x and then put the lower limit (${R_1}$) in place of $x$. Add the two terms together.

\[E = \dfrac{{\sigma y}}{{2{\varepsilon _o}}}\left[ { - \dfrac{1}{{(\sqrt {{R_2}^2 + {y^2}} )}} + \dfrac{1}{{(\sqrt {{R_1}^2 + {y^2}} )}}} \right]\]

**The electric field at any point distant y along the axis of the disk is \[E = \dfrac{{\sigma y}}{{2{\varepsilon _o}}}\left[ { - \dfrac{1}{{(\sqrt {{R_2}^2 + {y^2}} )}} + \dfrac{1}{{(\sqrt {{R_1}^2 + {y^2}} )}}} \right]\]. Hence option (C) is correct.**

**Note:**

The equation \[E = \dfrac{{\sigma y}}{{2{\varepsilon _o}}}\int_{{R_1}}^{{R_2}} {\dfrac{x}{{{{({x^2} + {y^2})}^{3/2}}}}} dx\] is of complex nature. Kindly be careful while doing the integration. Here we have to solve complicated integration as well as complicated variables, to make it simple put the complicated variable into a single variable and then solve for the integration.

Recently Updated Pages

Mark and label the given geoinformation on the outline class 11 social science CBSE

When people say No pun intended what does that mea class 8 english CBSE

Name the states which share their boundary with Indias class 9 social science CBSE

Give an account of the Northern Plains of India class 9 social science CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Advantages and disadvantages of science

Trending doubts

Bimbisara was the founder of dynasty A Nanda B Haryanka class 6 social science CBSE

Which are the Top 10 Largest Countries of the World?

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

10 examples of evaporation in daily life with explanations

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

How do you graph the function fx 4x class 9 maths CBSE

Difference Between Plant Cell and Animal Cell